MANAJEMEN PELAYANAN ISLAMI DALAM MENINGKATKAN KEPUASAN KONSUMEN DI TOKO ALFA BAROKAH KECAMATAN GAYAM KABUPATEN SUMENEP - Santi Ekawati; A. Muhyiddin Khotib (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2021)
The creation of consumer or customer satisfaction can make a harmonious relationship between service providers and customers. Since the establishment of the Alfa Barokah store, the needs of the community on the island of Sapudi have begun to be easy and easy to shop in meeting their daily needs. Provide and serve all the needs of the community in order to obtain financial and strengthen business management that is oriented towards service and obtaining halal profits, providing good customer service, providing all products for consumer needs. The discussion in this study is as follows: How is Islamic Management in increasing customer satisfaction at the Alfa Barokah store, Gayam District, Sumenep Regency? And what are the inhibiting and supporting factors in increasing customer satisfaction at the Alfa Barokah store, Gayam District, Sumenep Regency? Based on the results of research and studies that have been carried out by researchers, it shows that 1) Alfa Barokah Stores have treated consumers Islamically such as applying smiles, greetings and greetings to customers, paying attention to appearance and keeping clothes neat, having good and polite employees, providing some facilities and infrastructure and also respects customers like a king. 2) The inhibiting factor for the Alfa Barokah store is the slow delivery of goods due to weather factors. While the supporting factor is applying the attitude of Compliance, Reability, Empathy to customers.